Analisis Keragaman Fitoplankton di Sungai Barumun Kecamatan Panai Tengah Kabupaten Labuhanbatu - Sari Mawaddah Harahap; Arman Harahap (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2023)
Research on the analysis of the diversity of phytoplankton has been carried out in the Barumun River, Panai Tengah District, Labuhanbatu Regency. The Barumun River is widely used by the surrounding community for various activities, for example: disposal of industrial waste, household waste, fish auctions, ports, and fishing. This activity resulted in the Barumun River being polluted with increasingly turbid water color. The purpose of this study was to determine the diversity of phytoplankton in the Barumun River. This type of research is a descriptive research with a quantitative approach. Sampling used Plankton Net mesh size 30 μm from 3 stations with 10 repetition, observed using a microscope, identified using the book